The Relationship Between Problematic Internet Entertainment Use and Problem Solving Skills Among University Students - (:unkn) unknown (SPRINGER, 2014)
The current study aimed to investigate the relationship between Internet addiction and problem solving skills of university students. The study also examined the psychometric properties of the Turkish version of Problematic Internet Entertainment Use Scale for Adolescents, which centers on major Internet entertainments such as online video games and social networking sites, specifically with regard to normative, reliability, and validity information. Problem Solving Inventory was utilized in order to measure the problem solving skills of students. Both instruments were administered to 371 students aged 17 to 36 years from different departments in Marmara University and Istanbul Technical University (Istanbul, Turkey). This study showed that the Turkish version of the Problematic Internet Entertainment Use Scale for Adolescents was a reliable and valid instrument for measurement of maladaptive patterns in the use of online entertainments such as OVG and SNS. The results revealed that there is a close relationship between problematic internet entertainment use and Avoidant (r = 443; p < .01) and Impulsive problem solving styles (r = .402; p < .01) among university students.
Keywords: Problematic Internet entertainment use; Problem solving; University students; PSYCHOMETRIC PROPERTIES; ADDICTION; ADOLESCENTS; APPRAISAL; SYMPTOMS; SCALE